Evaluation of antimicrobial properties of polymer nanocomposites for medical application - Hopta, O. V.; Mishyna, M. M.; Syrova, A. O.; Makarov, V. O.; Avramenko, V. L.; МishurovD. O. (Regulatory Mechanisms in Biosystems, 2019)
The paper is devoted to the investigation of antimicrobial activity of polymer nanocomposites of both low-density polyethylene and nonwoven polymeric material (a mixture of woven and polyester fibers) that had been impregnated by Cu nanoparticles. The microorganisms were grown according to generally accepted microbiological rules and on media recommended for each bacteria family. Formation of biofilms of microorganisms was studied on the surface of microtiter plates for enzyme-linked immunosorbent assay. After incubation of microtiter plates, the culture medium was removed from the wells. The wells were rinsed five times with sterile distilled water. The plates were air dried for 45 minutes and each well was stained with 1% crystal violet solution in water for 45 min. After staining, the plates were washed with sterile distilled water five times. The quantitative analysis of biofilm production was done by adding 95% ethanol for discoloration of the wells. The research shows the antibacterial activity of Cu nanoparticles on planktonic forms of the investigated microorganisms, which prevented the formation of dense biofilms. With the use of low-density polyethylene impregnated by Cu the ability to form biofilms by planktonic cells of the referent strains of microorganisms was detected to decrease by 1.7 (Escherichia coli), 12.3 (Klebsiella pneumonia) times in the studied strains and with the use of nonwoven polymeric material treated by Cu nanoparticles, the ability to form biofilms decreased by 1.8 (Escherichia coli) – 21.8 (Klebsiella pneumonia) times in the studied strains. In subjecting the formed daily biofilms of referent strains of microorganisms to Cu nanoparticles, the destruction of biofilms of the studied strains of microorganism was observed as well as violation of the integrity of the biofilm monolayer and decrease of density index in comparison with control values. As a result, the obtained polymer nanocomposites can be recommended for preventive use in the fight against nosocomial infections. The practical relevance of this study lies in the possibility of reducing the incidence of purulent-inflammatory diseases and mycoses and, accordingly, reduction of the costs of treating these diseases.